PERSPEKTIF ISLAM DAN PERAWAT KOMUNITAS TERHADAP FENOMENA CHILDFREE PADA KALANGAN GEN Z - Apriliyani, Lika Sheilia; Zahra, Alinda Aura; Hanipah, Eva; Putri, Risma Indriani; Supriyadi, Tedi; Faozi, Akhmad; Suherman, Suherman (Universitas Mathla’ul Anwar Banten, 2025)
The phenomenon of childfree, namely the decision not to have children, has become an increasingly popular social issue among Generation Z. This decision is often influenced by economic factors, lifestyle, and lack of religious understanding, which gives rise to various pro and con opinions in society. This research aims to explore the perspectives of scholars and community nurses on this phenomenon, especially in providing a balanced view between religious and health aspects. The research uses a qualitative approach with a case study design, involving four participants from various backgrounds, namely two scholars, one community nurse, and one Generation Z individual, who resides in Sumedang. Data were collected through semi-structured online and offline interviews, then analyzed using Miles and Huberman's interactive methods that included data reduction, data presentation, and conclusion drawn. The results of the study show that the childfree phenomenon is influenced by economic uncertainty, social pressure, and the adoption of a modern mindset that emphasizes individual freedom and career priorities. The scholar's perspective highlights that the decision to be childfree is contrary to the purpose of marriage in Islam, which emphasizes the importance of the regeneration of the ummah and the blessing of having children. Meanwhile, community nurses noted reproductive health risks for women who choose childfree, including an increased risk of developing breast and cervical cancer in addition, childfree is also at risk of affecting demographic structures in the future, with a possible decline in the productive population. This study concludes that an integrated educational approach is needed, including premarial guidance that discusses financial aspects, reproductive health, and religious values, as well as government policies that support family welfare. With this approach, it is hoped that young couples can make wiser and more responsible decisions, thus maintaining a balance between individual rights, religious values, and generational sustainability.